2013
DOI: 10.1021/ac403676x
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Light-Up Probe for Parallel G-Quadruplexes

Abstract: Putative G-quadruplex-forming sequences (PQS) are highly prevalent in human genome; however, the structures and functions of most PQSs in genome are poorly understood. Therefore, selective recognition of certain types of G-quadruplexes (G4s) is important for the study of G4s. A new light up fluorescent probe, BPBC composed of benzimidazole and carbazole moieties was designed and synthesized. BPBC possesses a crescent-shaped π-conjugated planar core that is slightly larger than the dimension of the G-quartet pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
75
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(76 citation statements)
references
References 65 publications
1
75
0
Order By: Relevance
“…24 However, the affinities and uorescence enhancements are not directly correlated, due to the different microenvironments in the binding sites, which avoid the nonradiative relaxation process to different extents. 32 Here, we observed that these cyanine dyes could selfassemble aggregation and result in self-quenching in PBS, and also can recover high uorescence in the presence of G-quadruplex by transformation among different aggregations. It is well known that aggregation-caused quenching (ACQ) oen limits the label to analyte ratio and narrows the practical application.…”
Section: Comparison Of Spectral Changes Of Dyes Upon Binding Parallelmentioning
confidence: 70%
“…24 However, the affinities and uorescence enhancements are not directly correlated, due to the different microenvironments in the binding sites, which avoid the nonradiative relaxation process to different extents. 32 Here, we observed that these cyanine dyes could selfassemble aggregation and result in self-quenching in PBS, and also can recover high uorescence in the presence of G-quadruplex by transformation among different aggregations. It is well known that aggregation-caused quenching (ACQ) oen limits the label to analyte ratio and narrows the practical application.…”
Section: Comparison Of Spectral Changes Of Dyes Upon Binding Parallelmentioning
confidence: 70%
“…The Φ f values of QA and QAB greatly increased in the presence of parallel G-quadruplexes (EAD, Pu22, ckit2, and c-myc); and that of QAT and QAP increased in the presence of all forms of DNA. The Circular dichroism spectra of G-quadrplexes sequences in the presence of QAs did not show significant change ( Figure S5) compared with the CD spectra of these sequences in the absence of QAs [29,30], suggesting that the interaction of QAs with G-quadrplexes did not cause the conformation change of G-quadruplexes.…”
Section: Absorption Spectra Of Qas In the Presence Of Different Dnasmentioning
confidence: 97%
“…The fluorometric titration curves were further fitted to an independent-site model [29][30][31] (eq 1, Materials and Methods). All the data of QA/QAB against parallel G-quadruplexes fitted well by using 1:1 stoichiometry with R 2 higher than 0.98, however, the data of QAP and QAT could not satisfactorily fitted using any stoichiometry of 2:1, 1:1, 1:2 and 1:3…”
Section: Tablementioning
confidence: 99%
See 2 more Smart Citations